2021
DOI: 10.1002/hbm.25449
|View full text |Cite
|
Sign up to set email alerts
|

Neural processing of vision and language in kindergarten is associated with prereading skills and predicts future literacy

Abstract: The main objective of this longitudinal study was to investigate the neural predictors of reading acquisition. For this purpose, we followed a sample of 54 children from the end of kindergarten to the end of second grade. Preliterate children were tested for visual symbol (checkerboards, houses, faces, written words) and auditory language processing (spoken words) using a passive functional magnetic resonance imaging paradigm. To examine brain-behavior relationships, we also tested cognitive-linguistic preread… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 114 publications
(190 reference statements)
2
16
0
Order By: Relevance
“…A substantial line of research suggests that learning to read is accompanied by changes in ventral-temporal function during passive word reading tasks (Centanni et al, 2018;Chyl et al, 2018;Dehaene-Lambertz et al, 2018;Lerma-Usabiaga et al, 2018;Nordt et al, 2018;Kubota et al, 2019;Brem et al, 2020;Liebig et al, 2021). We, therefore, had expected to find a correlation between literacy and ventral-temporal activation during handwriting; however, we instead found a correlation between literacy and dorsal motor activation during handwriting.…”
Section: Activation In Lpips and Ldpg Correlates With Literacy In Childrenmentioning
confidence: 69%
“…A substantial line of research suggests that learning to read is accompanied by changes in ventral-temporal function during passive word reading tasks (Centanni et al, 2018;Chyl et al, 2018;Dehaene-Lambertz et al, 2018;Lerma-Usabiaga et al, 2018;Nordt et al, 2018;Kubota et al, 2019;Brem et al, 2020;Liebig et al, 2021). We, therefore, had expected to find a correlation between literacy and ventral-temporal activation during handwriting; however, we instead found a correlation between literacy and dorsal motor activation during handwriting.…”
Section: Activation In Lpips and Ldpg Correlates With Literacy In Childrenmentioning
confidence: 69%
“…The fusiform gyrus plays an important role for high-order visual processing in children and adults, including identification and differentiation of objects, 69 , 70 face recognition, 69 , 71 , 72 processing of colour information, 73–75 identifying words and letters from lower-level shape images, 74 , 76 , 77 and accessing object semantic information. 74 , 75 , 78 Furthermore, the LG has been shown to govern visual processing, 79 , 80 analysis of logical conditions, 80 , 81 and encoding of visual memories. 80 Normal visual function is important for brain maturation and cognitive development.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance, the activation of VWFA can be observed in adults with reading experience but not in illiterate adults, which may reflect access to orthographic representation during speech processing (Dehaene et al., 2015). It has also been revealed that children aged 9 but not 6 activate VWFA during native spoken language processing (Liebig et al., 2021; Monzalvo & Dehaene‐Lambertz, 2013). Consistent with these findings, the activation of the left OTC during speech has been repeatedly demonstrated in both school‐age children and adults under explicit requirements such as spelling and rhyming (Cone et al., 2008; DeMarco et al., 2017; Wang et al., 2018, 2020), and reduced activation was found in pre‐literate children and those with dyslexia (Conant et al., 2020; Desroches et al., 2010; Liebig et al., 2021; Raschle et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies have suggested that a reciprocal relationship occurs between speech and reading at the brain level (Dehaene et al., 2015). On the one hand, the speech processing system that includes the left temporoparietal cortex (TPC) and inferior frontal areas develops early in life and provides neural resources that can be recruited for acquiring reading skills later (Liebig et al., 2021; Lohvansuu et al., 2018). In line with this, individuals with dyslexia manifest impaired speech processing (Boets et al., 2007; Noordenbos & Serniclaes, 2015; Ziegler et al., 2009) and abnormal neural activity in regions including the left TPC (Landi et al., 2010; Lehongre et al., 2011; Lizarazu et al., 2020; Nora et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation